Sequence-specific DNA binding of individual cut repeats of the human CCAAT displacement/cut homeodomain protein. - Aufiero, B (1994)
CCAAT displacement protein (CDP), a nuclear protein of 180-190 kDa, contains a triplicated motif, the cut domain, similar (80-90% conserved) to three repeats of 60-65 amino acids first identified in Drosophila cut, a homeo-domain protein involved in cell-fate decisions in development. Cut repeats bind DNA and exhibit subtle differences in target-site recognition. DNA sequences specifically bound by cut repeats were isolated by PCR-mediated DNA target-site selection. Sequences selected for cut repeat 2 and 3 (CR2 and CR3) binding are A+T-rich and favor an ATA motif with similar, but not identical, flanking base preferences. CR2 and CR3 discriminate among similar target sequences. CR1, which is more divergent from CR2 and CR3, displays the most restricted pattern of DNA sequence recognition. Methylation interference analysis demonstrates different protein-DNA contacts for CR1 and CR3 binding to a target sequence. Thus, CDP/cut is a complex protein whose DNA-binding properties reflect the combinatorial interaction of four domains (three cut repeats and one homeodomain) with target DNA sequences.